The Influence of Exclusive Breastfeeding Education Based on Beauty and Wellness Approach with Booklet Media Approach on Breastfeeding Self-Efficacy of Lactating Mothers - Dewi Asmaul Husna; Eka Setyowati; Hartini Hartini (Indonesian Journal of Global Health Research, 2026)
Mother's milk (ASI) was a primary nutritional source that played an important role in infant growth and development as well as stunting prevention. The success of exclusive breastfeeding needed to be supported early through Early Breastfeeding Initiation (IMD) and comprehensive education provided to mothers from pregnancy until immediately after delivery. This research aimed to analyze the influence of exclusive breastfeeding education based on Beauty and Wellness Approach on breastfeeding self-efficacy in lactating mothers. The design used was quasi-experimental with pretest posttest with control group design The sampling technique used was non-probability sampling with purposive sampling method, so that a sample number of 32 respondents was obtained which was divided into intervention and control groups. The intervention group received exclusive breastfeeding education based on Beauty and Wellness through booklet media, while the control group received standard education according to routine services. Self-efficacy was measured using the Breastfeeding Self-Efficacy Scale. The Shapiro Wilk test showed that data were not normally distributed, so analysis used the Wilcoxon test for pre-post comparison and Mann-Whitney test for inter-group comparison. Results showed significant increases in self-efficacy in both groups, with greater increases in the intervention group (p = 0.003) compared to control (p = 0.041), and meaningful differences in score differences between groups (p = 0.032). Education based on Beauty and Wellness was proven to be more effective in increasing breastfeeding self-efficacy and had potential to support the success of exclusive breastfeeding.